Evaluation of serum NGAL and hepcidin levels in chronic kidney disease patients. (2nd January 2016) - Avci Çiçek, Esin; Rota, Simin; Dursun, Belda; Kavalci, Emine
Abstract: Cardiovascular disease is the major cause of death in chronic kidney disease (CKD) patients. The main underlying reason is inflammation. In CKD, interleukin-6 and hypersensitive C-reactive protein are known to be used for the evaluation of inflammation and serum levels increase with decreased creatinine clearance. Neutrophil gelatinase-associated lipocalin (NGAL) and hepcidin are also considered to be effective in the assessment of inflammatory conditions. The possible interactions of NGAL and hepcidin with inflammatory markers in CKD patients including the kidney transplants, which have not been thoroughly explained up to date wereevaluated in this study. Serum creatinine, iron, unsaturated iron binding capacity, interleukin-6, hypersensitive C-reactive protein, NGAL, hepcidin and pro-hepcidin levels were measured in a cohort of 163 CKD patients including transplant patients and 82 healthy volunteers. Clinical evaluation and classification of the patients were done according to the NFK/KDOQI guideline. Serum hepcidin, Prohepcidin, NGAL, hypersensitive C-reactive protein and interleukin-6 levels were higher in patient groups compared to the control group. In patient groups, while hepcidin, NGAL, interleukin-6, hypersensitive C-reactive protein levels were correlated with creatinine and glomerular filtration rate, iron metabolism parameters were not correlated with the inflammation biomarkers. Inflammation related hepcidin and NGAL weakly correlated with creatinine clearance. Our results demonstrated that serum NGAL and hepcidin levels might be valuable for the evaluation of inflammation in CKD, and these new inflammation parameters are not related through iron metabolism.